Influence of V2O5 Addition on the Magnetic and Electrical Properties of Iron-Deficient Ni-Zn Ferrite - Akther, Shireen; Choudhury, Md Amanullah; Rahman, Jalalur (Journal of Bangladesh Academy of Sciences, 2010)
The influence of V2O5 addition on the magnetic and electrical properties of iron deficient ferrites with composition: Ni0.65Zn0.35Fe1.96O4+xV2O5 have been investigated, where values of x (in mol unit) are 0, 0.002, 0.004, 0.006, 0.008 and 0.01. The sintered density, saturation magnetization, Curie temperature of the samples increase up to V2O5 (x=0.004) and then decrease. The addition of V2O5 to the composition of ferrite increases the anion vacancy concentration, prohibit the discontinuous grain growth, which in turn enhances the density. The increment of saturation magnetization is due to the enhancement of resultant sublattice magnetic moment and density. Upto V2O5 (x=0.004), V2O5 goes into solid solution with the ferrite matrix and increases the Curie temperature. This is probably due to ions occupy some octahedral sites (B-sites) of the ferrite lattice by V5+ , as a result some Fe3+ ions may come out from octahedral to tetrahedral sites (A-sites) thereby increasing A-B interaction and hence the Curie temperature. The dc resistivity of all the samples increases with the increment of V2O5 in the compound. DOI: 10.3329/jbas.v33i2.4097 Journal of Bangladesh Academy of Sciences, Vol. 33, No. 2, 145-149, 2009